Karakteristik Karya Ulama Purworejo - Novita Siswayanti (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
This paper aims at studying and identifying the characteristic of ulama’s works from Purworejo, Central Java Province of Indonesia. Some ulama from Purworejo teach their students as well as their followers by publishing their idea based on religious texts. They try to response the problem of ummat from daily life perspectives. Those works consist of 56 titles at least that being written in Arabic language, Indonesian languange as well as Javanese language. The scope of works the have written are also varied ranging from discussing a certain doctrine to compiling some religious text for daily ritualpurposes. Through qualitative method, this paper shows that most of ulama articles from Purworejo targeting them for internal members although only a commercial publication company has published a few.